Histopathological changes of the nasal mucosa in active and retired nickel workers. - Torjussen, W. (Nature Publishing Group, 1979)
Histological examinations were made on nasal biopsy specimens from the middle turbinate in 318 active and 15 retired nickel workers and in 57 controls, to study the prevalence of nasal carcinoma or possible precancerous mucosal changes in nickel-exposed individuals. The histopathological changes were evaluated according to a point-score scale, and the results were correlated to age, smoking habits, duration and type of nickel exposure and to nickel concentrations in nasal mucosa, plasma and urine. The explanatory values of these factors on the histopathology were estimated by stepwise multiple regression analysis. Two nickel workers from the roasting/smelting department (0.6%), both employed 28 years at the plant, had nasal carcinoma. Epithelial dysplasia was found in about 12% of active and 47% of retired nickel workers. One of the controls, a male carpenter, had dysplasia. These histopathological changes may be precancerous lesions, as they are almost exclusively found in active and retired nickel workers with enhanced risk of nasal carcinoma. Loss of respiratory epithelium and development of squamous epithelium were regarded as unspecific histopathological changes. These changes were seen in all groups, even though in significantly higher incidence in the nickel-exposed groups. Duration of nickel exposure, type of nickel-refining work and tobacco consumption were the independent variable that, taken altogether, had the highest explanatory values for the histopathological changes. IMAGES: